Annual Plan 1997-98 Volume-VI Sector: General Services Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1997)
Some departments of the Administration are Functioning in old building in delabidated condition. These departments are requiring now building. Also some departments which had expanded needs additional accommodation.
Andaman and Nicobar Administration, Planning Department
Sector General Services